Evaluating Multicultural Educational Experiences and Intercultural Communication Competence in an Arab Context - Al-Sumait, Fahed (2022)
As an expatriate-majority state with a diverse multicultural and multilingual environment, Kuwait offers a distinctive opportunity for examining intercultural communication competence (ICC). This study examines the extent to which cognitive, affective, and behavioral predispositions toward ICC are present within the context of higher education by examining multilingual student populations at three local universities. Using survey data from over 800 respondents, the study explores ICC correlates such as linguistic abilities, formal educational experiences, and other sociodemographic factors. Analyses of variance demonstrate that some expected factors, such as multilingualism or expatriate status, contributed positively to ICC measures, while others did not—including attending English-language universities. Years of university experience positively correlated with both affective and behavioral aspects of ICC, while the cognitive component was least affected. Practical implications include the opportunity for universities to incorporate more cognitive-oriented intercultural lessons into their curricular objectives, which can add both educational and social value.